Elsie Clews Parsons : inventing modern life - Deacon, Desley (University of Chicago Press, 1997)
Elsie Clews Parsons was a relentlessly modern woman. A pioneering feminist, an eminent anthropologist, an ardent social critic, she challenged Americans to develop flexible and dynamic gender, family, and social arrangements that fit the new century. From 1912, when she incorporated ethnographic data on upper-class New York into a series of tersely ironic books and articles, Parsons brought to anthropology a passionate desire to educate the public to accept and welcome sexual and social diversity. Desley Deacon's vibrant and richly detailed biography examines the powerful connections linking Parsons's intellectual commitments to her extraordinary life experience. A wealth of correspondence and memoirs allows Deacon to vividly reconstruct Parsons's unconventional marriage, her intimate friendships, her ties to a burgeoning avant-garde, her wide-ranging travels, and her bitter attempts to escape the stifling conventions of New York's social elite - in short, all of her efforts to overcome gender biases in both academia and society. There is an immediacy to Parsons's struggles, a context to her modernism, and an urgency to her message. Her remarkable intensity compelled her to redefine the social and sexual values of her day, to explore gender roles in other cultural settings, and to thoroughly detonate, through word and deed, entrenched nineteenth-century conceptions of women, civilization, and morality. In Elsie Clews Parsons, Deacon has fashioned a deeply insightful portrayal of an uncommon woman with the uncommon courage to radically reconstruct sexual identity, for herself and for the modern age.
Keywords: Parsons, Elsie Worthington Clews, -- 1874-1941.; Parsons, Elsie Worthington Clews, -- 1874-1941; Women Indianists -- United States -- Biography.; Women anthropologists -- United States -- Biography.; Women social scientists -- United States -- Biography.; Feminists -- United States -- Biography.; Feminism -- United States -- History.; Sex role -- United States -- History.; United States -- Intellectual life -- 20th century.; United States -- Race relations.; United States -- Social conditions.; Femmes amérindianistes -- États-Unis -- Biographies.; Femmes anthropologues -- États-Unis -- Biographies.; Femmes spécialistes des sciences sociales -- États-Unis -- Biographies.; Féministes -- États-Unis -- Biographies.; Féminisme -- États-Unis -- Histoire.; Rôle selon le sexe -- États-Unis -- Histoire.; États-Unis -- Vie intellectuelle -- 20e siècle.; États-Unis -- Relations raciales.; États-Unis -- Conditions sociales.; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists.; SOCIAL SCIENCE -- Regional Studies.; SOCIAL SCIENCE -- Anthropology -- General.; Feminism; Feminists; Intellectual life; Race relations; Sex role; Social conditions; Women anthropologists; Women Indianists; Women social scientists; United States; 1900-1999; Biographies; History; Biographies.